Detection of Bifidobacteria Breve by Indirect Enzymelinked Immunosorbent Assay (Elisa) - Tee, Siew Choon (2001)
In this study, the suitability of fructose-6-phosphate phosphoketolase (F6PPK) from Bifzdobacterium breve, and intact B. breve cells were examined as immunogens for the production of polyclonal antibodies that could be used to detect the presence of the organism. F6PPK is the enzyme that catalyzes the breakdown of fructose-6-phosphate to yield erythrose-4-phosphate and acetyl phosphate through the bifid shunt. It represents an interesting candidate as it is the key enzyme found restricted to bifidobacteria, and there are differences in molecular masses of the enzyme among human and animal sources. The study involved two stages. In the first stage, F6PPK extracted from B. breve was partially purified by sequential acetone-fractionation, ion-exchange chromatography and gel filtration chromatography, and then characterized. F6PPK was eluted from the anion exchanger column at 0.48 mM NaCl. Following purification by the gel filtration chromatography, the specific activity of F6PPK was found to be 11.05 fold but only 0.4% was recovered. The enzyme was not purified to homogeneity since 2 protein bands were observed on native polyacrylamide gel electrohphoresis. The apparent molecular mass of the enzyme as determined by gel filtration chromatography on Superose 12 was 200,000 Daltons. The enzyme was stable, at least for 10 minutes, between 20-50°C. The optimum temperature was 37°C. It has a pH optimum of pH 6.0. F6PPK is not a metalloenzyme since EDT A did not reduce its activity. Cations like magnesium and calcium affected the activity of the enzyme. The thioI inhibitors Lcysteine and hydroxylamine HCl, were strongly inhibited activity of F6PPK by 19.8% and 17.1% respectively. The affinity constant, Km, of F6PPK was 2xlO-1 mM and maximal velocity, V max was 20 µmole/min with fructose-6-phosphate as the substrate. In the second stage of this study, the production of polyclonal antibodies was achieved by injecting F6PPK obtained after gel filtration and intact cells of B. breve intradermally into 5 New Zealand White Rabbits, three of the rabbits were injected with F6PPK. Booster doses made in Freund Incomplete Adjuvant were adminjstered every two weeks for a total of three times. Blood was collected once before the first injection and twice after third booster and labeled as Bleed 1, Bleed 2 and Bleed 3, respectively. Assessments of the antisera were carried out by Noncompetitive Indirect ELISA. Bleed 2 contained the highest level of antibody. Extensive checkerboard htration was performed; the optimum antiserum dilution for anti-F6PPK antiserum was 1:1600, while the anti-B. breve antiserum dose-response was 1:800 and conjugate antibody was used at a dilution of 114000. The best absorption for both antisera were obtained using phosphate buffered saline pH 7.2 as the coating buffer. Crude extract was good enough to bind to the anti-F6PPK antiserum. Both antisera were capable of detecting bifidobacteria at the species level at 1 x 10⁵ CFU/ml or greater. Both antisera were found to cross-react with the different strains of B. breve. A slight cross-reaction occurred with other Bifidobacterium spp. whereas they showed no significant cross-reactivity towards LactococCUs spp., Lactobacillus spp., probiotics, yogurt starter cultures and E. coli. ELISA described herein should allow unequivocal identification of B. breve.